Telehepatology Use and Satisfaction Among Vulnerable Cirrhosis Patients Across Three Healthcare Systems in the Coronavirus Disease Pandemic Era - Priyanka Athavale; Robert J. Wong; Derek D. Satre; Alexander Monto; Ramsey Cheung; Jennifer Y. Chen; Steven L. Batki; Michael J. Ostacher; Hannah R. Snyder; Brigita D. Widiarto; Seo Yoon Oh; Meimei Liao; et al. (Gastro Hep Advances, 2024)
Background and Aims: Telehealth has emerged as an important mode of cirrhosis care delivery, but its use and satisfaction among vulnerable populations (eg, racial/ethnic minorities, socioeconomically disadvantaged, substance use disorders) are unknown. We evaluated digital capacity, telehealth use, satisfaction and associated factors among patients receiving hepatology care via telehealth (telehepatology) across 2 Veterans Affairs and 1 safety-net Healthcare systems. Methods: English- and Spanish-speaking adults with cirrhosis (N = 256) completed surveys on telehealth use and satisfaction, quality of life, pandemic stress, alcohol use and depression. Logistic regression analyses assessed telehealth use and general linear models evaluated telehealth satisfaction. Results: The mean age was 64.5 years, 80.9% were male and 35.9% Latino; 44.5% had alcohol-associated cirrhosis; 20.8% had decompensated cirrhosis; 100% had digital (phone/computer) capacity; and 75.0% used telehepatology in the prior 6 months. On multivariable analysis, participants with alcohol-associated (vs not) cirrhosis were less likely and those with greater pandemic stress were more likely to use telehepatology (odds ratio = 0.46 and 1.41, respectively; P < .05). Better quality of life was associated with higher telehepatology satisfaction and older age was associated with lower satisfaction (β = 0.01 and −0.01, respectively; P < .05). Latinos had higher satisfaction, but alcohol use disorder was associated with less satisfaction with telehepatology visits (β = 0.22 and −0.02, respectively; P < .05). Conclusion: Participants had high telehepatology capacity, yet demographics and alcohol-related problems influenced telehepatology use and satisfaction. Findings underscore the need for interventions to enhance patient experience with telehepatology for certain vulnerable groups including those with alcohol-associated cirrhosis in order to optimize care delivery.